2009
DOI: 10.4049/jimmunol.0803030
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Epitope of Protein Inhibitor of Activated STAT3 Is Responsible for the Induction of Apoptosis in Rat Transformed Mast Cells

Abstract: Protein inhibitor of activated STAT3 (PIAS3) functions in vivo as a key molecule in suppressing the transcriptional activity of both microphthalmia transcription factor (MITF) and STAT3, two transcription factors that play a major role in the development, phenotypic expression, and survival of mast cells and melanocytes. In the present study we have investigated the role played by PIAS3 in the regulation of cell cycle in mast cells and melanocytes. We have characterized the biological role of a 23-aa domain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…It was therefore reasonable to postulate that PIAS3 and STAT3 might interact through similar domains. However, a previous report showed that an NH 2 -terminal fragment of mPIAS3, comprising amino acid positions 82 to 132, interacts with STAT3 in murine cell lines (15,29). We performed yeast two-hybrid analyses with the NH 2 terminal (amino acid positions 1-319) and the COOH terminal (amino acid positions 320-619) fragments of hPIAS3.…”
Section: Delimitation Of the Pias3 And Stat3 Interaction Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was therefore reasonable to postulate that PIAS3 and STAT3 might interact through similar domains. However, a previous report showed that an NH 2 -terminal fragment of mPIAS3, comprising amino acid positions 82 to 132, interacts with STAT3 in murine cell lines (15,29). We performed yeast two-hybrid analyses with the NH 2 terminal (amino acid positions 1-319) and the COOH terminal (amino acid positions 320-619) fragments of hPIAS3.…”
Section: Delimitation Of the Pias3 And Stat3 Interaction Domainsmentioning
confidence: 99%
“…A few studies have addressed the effects of exogenous PIAS3 overexpression in cancer cells: (a) about 89% of glioblastoma samples were found to be PIAS3 negative and P-STAT3 positive and the ectopic expression of PIAS3 in a glioblastoma cell line caused the inhibition of the transcriptional activity of STAT3 (14); (b) overexpression of PIAS3 in melanoma and lung cancer cell lines inhibited cell growth and suppressed STAT3 activity (15,16); (c) overexpression of PIAS3 in v-Src-overexpressing tumor cells suppressed STAT3 target gene expression (17); (d) exogenous expression, mediated by infection with an adenovirus encoding kChaP/PIAS3β in prostate cancer cells, induced apoptosis and reduced growth of prostate tumor xenografts in nude mice (18). These studies indicate that PIAS3 can counteract the function of constitutively active STAT3.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that miR‐181b directly bound to the PIAS3 3′UTR and inhibited the expression of PIAS3, and PIAS3 suppression contributed to the activation of STAT3. The proline, isoleucine, asparagine, isoleucine, threonine (PINIT) motif is one of several conserved domains of the PIAS family 37, 38. The PINIT domain allows nuclear translocation of PIAS337, 38 and it is known to promote STAT3‐PIAS3 interaction 39.…”
Section: Discussionmentioning
confidence: 99%
“…The proline, isoleucine, asparagine, isoleucine, threonine (PINIT) motif is one of several conserved domains of the PIAS family 37, 38. The PINIT domain allows nuclear translocation of PIAS337, 38 and it is known to promote STAT3‐PIAS3 interaction 39. A short stretch of 50 amino acids in the PINIT domain of PIAS3 (PIAS3 82‐132 ) can directly interact with STAT3 and down‐regulate STAT3‐dependent transcriptional activity 37, 38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation